Does a Country’s Risk Factors Impact in Spreading COVID-19 in African Countries? - Venkatachary, Sampath Kumar; Prasad, Jagdish; Samikannu, Ravi; Baptist, Leo John; Alagappan, Annamalai; Ravi, Rohini; Imaculate, Anitha (International Review of Management and Marketing, 2020)
The novel coronavirus or COVID-19 has extended its spread across the globe, and most of the countries have reported infections. In what started as a first case single reported in Egypt has now magnified and close to about 355000+ infections have been reported across the African region as on 26-6-2020. The transmission trajectory of COVID-19 across the globe remains a mystery, and much remains to be learned. The fear of spread among nations is a cause for concern, especially among African countries with weaker governance, high poverty levels, weak health systems etc. The density of population in urban areas could be a trigger factor and could be devastating. The management and control of COVID-19 are critical to check the spread, and most of it is reliant on the health facilities in countries to carryout repeated tests. This paper aims to analyses the various parameters and tabulates a risk matrix and places it analysis using SPSS based on the available data. The analysis also provides potential insight into the vulnerabilities among African countries and a relative review of factors associated with the novel coronavirus. Keywords: SPSS, Risk Matrix, COVID-19, Pandemic, SARS, MERS JEL Classifications: I0; I1; I2; C0 DOI: https://doi.org/10.32479/irmm.10321